Unraveling pH dependent cycling stability of ferricyanide/ferrocyanide in redox flow batteries. (December 2017) - Luo, Jian; Sam, Alyssa; Hu, Bo; DeBruler, Camden; Wei, Xiaoliang; Wang, Wei; Liu, T. Leo
Abstract: K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] have been frequently applied in redox flow batteries to achieve sustainable and economical renewable energy storage. However, fundamental knowledge of the redox couple of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] regarding their flow battery performance is largely underdeveloped. Herein, we present a comprehensive study on the fundamental properties and electrochemical kinetics of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] in aqueous supporting electrolytes at different pH values. Particularly, the charge/discharge cycling stability of the redox couple was evaluated at different pH values using a half-cell flow battery configuration. The battery results unambiguously confirmed that the redox couple functions best at neutral or near neutral conditions. Dramatic capacity decay of the redox couple was observed in a strong alkaline KOH electrolyte (pH =14), which is due to the chemical decomposition associated with the CN - ligand dissociation. The presented study not only advances an in-depth understanding of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] regarding their flow battery applications but also highlights the challenge of acid-base side reactions of redox active molecules applied in aqueous acidic/alkaline redox flow batteries. Graphical abstract: Highlights: A comprehensive fundamental understanding of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] is presented. Supporting electrolytes affect physical/chemical properties of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ]. The [Fe(CN)6 ] 3-/4- redox couple functions best at neutral or near neutral conditions. .The challenge of acid-base side reactions in redox flow batteries was emphasized.